Anatomical basis of diverse jaw protrusion directionality in ponyfishes (Family Leiognathidae). (13th January 2021) - Roberts, Alexus S.; Hodge, Jennifer R.; Chakrabarty, Prosanta; Wainwright, Peter C.
Abstract: Protrusion of the oral jaws is a key morphological innovation that enhances feeding performance in fishes. The mechanisms of protrusion and the basis of variation in its magnitude are well studied, but little attention has been paid to the functional morphology of protrusion directionality, despite wide variation among teleost species from slightly dorsal to strongly ventral. Ponyfishes (Leiognathidae) comprise a group of 52 species that exhibit striking diversity in the directionality of jaw protrusion, providing a promising system for exploring its underlying basis in a single clade. We examined the anatomical basis of protrusion directionality by measuring eight traits associated with the size and positioning of oral jaw bones. Measurements were made on cleared and stained specimens of 20 ponyfish species, representing every major lineage within the family. Species fell into three nonoverlapping clusters with respect to directionality including dorsal, rostral, and ventral protruders. A key correlate of protrusion direction is the anterior–posterior position of the articular‐quadrate jaw joint. As the joint position moves from a posterior to a more anterior location, the orientation of the relaxed mandible rotates from an almost horizontal resting position to an upright vertical posture. Abduction of the mandible from the horizontal position results in ventrally directed protrusion, while the more upright mandible rotates to a position that maintains dorsal orientation. The resting orientation of the premaxilla and maxilla, thus, vary consistently with protrusion direction. Mouth size, represented by length of the mandible and maxilla, is a second major axis of variation in ponyfishes that is independent of variation in protrusion directionality. Abstract : Leiognathids comprise a group of 52 acanthomorph species that exhibit striking craniofacial diversity. Direction of oral jaw protrusion, which correlates strongly with the anterior–posterior position of the articular‐quadrate joint, represents a major axis of variation in this clade, with species that protrude their jaws in either a ventral (top left), rostral (bottom), or dorsal (top right) direction. Mouth size also represents a major axis of variation in ponyfishes that is independent of variation in protrusion directionality.